LOKAPALADHAMMA: MANAGEMENT PRINCIPLES TO PREVENT CORRUPTION IN THAI SOCIETY IN A SUSTAINABLE MANNER - Nanthapanyo/ Chaisangka , Phramaha Surasit (Journal of Buddhist Education and Research (JBER), 2024)
Corruption is the use of power acquired or misuse of existing assets. for the benefit of oneself, family, friends, acquaintances, or any other undue benefits which cause damage to the interests of others. Principles of Sustainable Corruption Prevention is to apply the principles of Buddhism to cultivate the mind and behavior. The Dharmma protecting the world or Dharmma Lokapala is a principle that aims for the world society to live in peace, free from corruption, honesty, and have a public mind. which includes hiri, self-ashamedness for doing wrongdoings Against all dishonest conduct and self-humiliation to refrain from doing good that should have been done in oneself. is fair to protect the world make the world peaceful make people live in peace. and Ottappa, the fear of the consequences of evil. To the consequences of corruption, Ottappa is a symptom of the mind that is shaken when doing evil. because of fear of wrongdoing that will result later It can happen because you think about the punishment or suffering that will come from doing evil. from their corrupt behavior. Ottappa is the Dharma that protects the world with Hiri. Because people with ottappa are afraid to make mistakes. cause to refrain from various behaviors that cause peace and happiness Sustainable peace in the world.